What's in a message: A systemic functional analysis of cancer prevention messages. (17th July 2021) - Jerome, Collin; Ting, Su‐Hie
Abstract: This article provides some insights on how a particular reading from a theoretical framework can bring out details and problems with health communication posters. Using Michael Halliday's Systemic Functional Linguistics (SFL) framework, the article examines cancer prevention messages in cancer posters produced by the Ministry of Health Malaysia. The analysis shows that the posters organize and convey their intended messages through the realization of the three strands of meaning or metafunctions—the ideational, the interpersonal, and the textual—by drawing on the grammatical resources of the language used. Such meanings are created and expressed throughout the three main sections of the posters; the heading, the body of the text, and the signature line. Despite its practical limitations in particular linguistic contexts, the article shows that SFL is a useful tool for the analysis of Malaysia's cancer posters and how it can potentially provide a more nuanced understanding of the country's ongoing health risk communication initiatives. Abstrak: Artikel ini memberi beberapa pandangan mengenai bagaimana bacaan tertentu dari satu kerangka teori dapat mengemukakan perincian dan masalah berkenaan poster komunikasi kesihatan. Dengan menggunakan kerangka Linguistik Sistemik Fungsional (LSF) oleh Michael Halliday, artikel ini mengkaji mesej pencegahan kanser dalam poster‐poster kanser yang dihasilkan oleh Kementerian Kesihatan Malaysia. Analisis menunjukkan bahawa poster berkenaan menyusun dan menyampaikan mesej yang dimaksudkan melalui penrealisasian tiga lembar makna atau metafungsi—ideasional, interpersonal, dan tekstual—dengan mengembleng unsur nahuan bahasa yang digunakan. Makna‐makna tersebut dicipta dan dipersembahkan menerusi tiga bahagian utama poster; tajuk, kandungan teks, dan garis tandatangan. Walaupun terdapat limitasi praktikal dalam konteks linguistik tertentu, LSF merupakan satu alat yang berguna untuk menganalisis poster kanser Malaysia dan bagaimana ia berpotensi untuk memberi pemahaman yang lebih bernas terhadap inisiatif komunikasi risiko kesihatan yang berterusan di negara ini.